Iron Status in Male Type 2 Diabetic Patients and Its Association with Their Glycemic Status (Ibrahim Cardiac Medical Journal, 2024)
Background & objective: Alteration in iron metabolism may occur in diabetic patients especially those who have poor glycemic control. Serum iron is involved in free radical formation associated with hyperglycemia and causes diabetic complications. The present study was undertaken to observe the iron status and its relation with glycemic control in male type 2 diabetic patients.Methods: This cross-sectional analytical study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from July 2017 to June 2018. A total of 48 diagnosed male type 2 diabetic patients (cases) were recruited from the Out-patient Department (OPD) of Endocrinology based on predefined eligibility criteria. Of them, 24 had good glycemic control (HbA1c level < 7%) (Group B1) and 24 had poor glycemic control (HbA1c level ≥ 7%) (Group B2). To compare the outcome (serum iron status) of these diabetic patients, another 48 age- and BMI-matched healthy non-diabetic male subjects were selected from personal contact as control. While diabetes and glycemic status (fasting blood glucose level, and HbA1c) of the diabetic patients were exposure variables, serum iron, serum total iron binding capacity (TIBC), transferrin saturation, and serum ferritin were the outcome variables.Results: The mean age of the subjects of either study group was around 43 and there was no significant difference between the groups concerning age (p = 0.610). The distribution of BMI and serum creatinine between groups was also similar (p = 0.135 and p = 0.134 respectively). The cases had a significantly higher level of serum iron, transferrin saturation, and an insignificantly lower total iron binding capacity (TIBC) than their non-diabetic peers (p = 0.045, p = 0.036, and p = 0.061 respectively). A comparison of outcome variables among the three groups shows that the groups were significantly heterogeneous in terms of serum iron, TIBC, transferrin saturation, haemoglobin level (p = 0.032, p = 0.012, p = 0.008 and p = 0.018 respectively). The associations were more conspicuous in patients with poor glycemic status. Correlation analyses revealed that while there was a significant linear correlation between serum iron and HbA1c (r = + 0.376, p < 0.01), it was negatively correlated with serum TIBC (r = -0.478, p < 0.001). The glycemic status (HbA1c) was also found to be linearly correlated with serum ferritin and transferrin saturation (r = + 0.354, p = 0.013 and r = + 0.462, p < 0.001 respectively).Conclusion: The study concluded that type 2 diabetic patients have a significantly higher level of serum iron, transferrin saturation, and a lower total iron binding capacity (TIBC) than the non-diabetic healthy subjects, all of which may lead to reduced synthesis of hemoglobin. The compromised iron metabolism is even more evident as the hyperglycemia aggravates.Ibrahim Card Med J 2023; 13 (1&2): 32-39